Sensitivity analysis of tangential digging forces of the bucket wheel excavator SchRs 1320 for different terraces - Gottvald, Jakub; Kala, Zdenek (Journal of Civil Engineering and Management, 2012)
Researches in the field of economy of control of mining processes of minerals are continually met with a number of unsolved and newly arising problems. New deposits of brown coal are located at greater depths than before and are more difficult to mine. Problems in the field of rock mining stem from the greater diversity of rocks in mining, and it results in more difficult mining conditions. On the other hand, even greater demands are made to decrease the economic demand of mining. Current research is aimed at the most optimal utilization of energy provided on the bucket wheel of excavators, such that the energy demand of the mining process decreases, whilst preserving maximum performance. These requirements place greater demands on the precision of planning of mining and maximum economic efficiency. The presented article illustrates the possibilities of the utilization of Sobol sensitivity analysis during the investigation of the influence of the parameters of mining processes on tangential digging forces. Analyses are carried out for the mining process of bucket wheel excavator SchRs 1320. For purposes of the study, detailed measurements of operational parameters were performed on the excavator during a whole work cycle.